An Exasperating and Unusual Presentation of Buschke-Lowenstein Tumor in an Adolescent Girl: Case Report with Review of Literature - Nanda, Sony; Mohapatra, Janmejaya; Mahapatra, Manoranjan; Parija, Jita; Nayak, Bhagyalaxmi (Indian Journal of Medical and Paediatric Oncology, 2024)
Giant condylomata acuminata of Buschke-Löwenstein (GCBL) is a benign condition with a high recurrence rate and a remote possibility of developing into cancer. It is characterized by excessive proliferation of verrucous lesions on the genitalia and/or perianal region, and is frequently linked to human papillomavirus (HPV) subtypes 6 and 11. With the exception of a few case series, case reports make up the majority of the literature. Despite the literature's support for surgical excision, the current evaluation reveals a lack of clarity regarding the disease's diagnosis and best course of action. Better assessment and management of these patients are necessary to prevent any progression/recurrence of disease.Here, we present a case of a GCBL of the vulva in an 18-year-old girl, who was effectively treated with a simple vulvectomy and split skin graft reconstruction. The reported case is one of the rarest presentations of Buschke-Löwenstein tumor as it is not associated with any of the HPV subtypes and is seen in an 18-year-old girl, one of the youngest patients reported till date. This case report is followed by a brief review of the literature on GCBL, which will add to our understanding of this entity and the most effective therapy to treat the disease.
Keywords: giant condylomata acuminata; Buschke-Löwenstein tumor; human papillomavirus; adolescent; verrucous hyperplasia